Surface characterization of wood treated with boron compounds combined with water repellents. Issue 3 (12th February 2019) - Can, Ahmet; Sivrikaya, Hüseyin
Abstract: Longer weathering exposure periods are more reliable for end‐use performance evaluations of wood surfaces. This study aimed to investigate the effect of boron impregnation on the surface composition and color of Scots pine ( Pinus sylvestris L.) wood exposed to 18 months of natural weathering in the West Black Sea Region of Turkey. All measurements were performed at 6 month intervals. Samples were first impregnated with boron compounds and then for a second time using five different water‐repellent materials. Polyethylene glycol and aluminum sulfate were introduced with the boric acid as single impregnations. With increased weathering time, the samples darkened, while sodium silicate kept the color change to a minimum. Nano boron‐impregnated samples exhibited more effective results than those impregnated with boric acid. The FTIR analysis results demonstrated that the impregnation process had caused significant changes in the chemical structure of the samples. The changes in the chemical structure of the wood resulting from the impregnation process were partially maintained during the weathering.